To the 80th Anniversary of Professor V.A. Kitaev - Oleg Kuznetsov (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2022)
The article was prepared for the 80th anniversary of the doctor of historical sciences, professor Vladimir Anatolyevich Kitaev. Student of the outstanding soviet historian P.A. Zaionchkovsky, graduate of Gorky State University V.A. Kitaev is an authoritative expert in the field of social movement and public thought in Russia of the 19th century. V.A. Kitaev revealed and convincingly proved that the Russian thought of the 19th century sought answers to topical political and socio-economic issues on the path of ideological synthesis. Conservatism contained elements of liberalism (slavophiles); Russian liberals have not escaped the influence of conservative ideas (K.D. Kavelin, B.N. Chicherin); the journal “Bulletin of Europe” became the ancestor of social liberalism in Russia; one of the leaders of the decembrists, P.I. Pestel, in his constitutional draft attempted to combine liberalism, conservatism, and socialism. The article suggests that such an ideological synthesis could be a reflection of the ideas of the Russian people, which contained the age-old dreams of freedom and the pursuit of it, commitment to traditional national and state values, thirst for social justice. In 1983–1999 V.A. Kitaev worked at Volgograd State University. He was the first dean of the Faculty of History and permanent head of the Department of Russian History. Under his leadership the traditions of the Faculty of History (now the Institute of History, international relations and social technologies) were laid. Now V.A. Kitaev is a professor at Nizhny Novgorod State University.